Study Of The Propagation Of Short Pulse Laser With Cavity Using Numerical Simulation Software - Terniche, S.; Kellou, A.; Kermaoui, A.; Si Fodil, R.; Becheker, R. (University of Eloued جامعة الوادي, 2012)
The purpose of this representation is to show the potentialities (Computational Time, access to the dynamic and feasibility of systematic studies) of the numerical study of the nonlinear dynamics in laser cavity, assisted by software. We will give as an example, one type of cavity completely fibered composed of several elements and then studying the physical parameters of a pulse propagating into this cavity, determining its characteristics at the output. The results are interesting but we also projects to verify them experimentally by making assemblies similar to this type of cavities.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 01
Keywords: Optical fiber, short pulse, bandwidth, spectral width.